NILAI PITUTUR JAWA DALAM KARYA TARI WAYANG SUKET PUSPA SARIRA - Alif Laili Ramadhani Ilaah Nur; Cipto Budy Handoyo (JURNAL PAKARENA, 2026)
This study aims to examine the construction of meaning and values embedded in the dance work and its implications for dance arts education. A descriptive qualitative method was employed, with data collected through in-depth interviews and documentation. The findings reveal that Puspa Sarira constructs meaning through three philosophical dimensions: ontologically, the dancer's body is positioned as a symbolic space radiating inner values; epistemologically, the learning process encourages understanding through direct experience and reflection; and axiologically, every element of the work carries noble values including humility, empathy, independence, solidarity, and the aspiration for holistic well-being. Each of the ten documented dance movements contains pitutur messages encoded through gesture, formation, the white kelir screen property and wayang suket, and song lyrics. These findings imply that Puspa Sarira is suitable for integration as a local wisdom-based dance learning material at the junior high school level, while simultaneously serving as an active preservation effort for the endangered wayang suket tradition. This research contributes to the development of an arts education paradigm oriented not merely toward technical skill, but toward the formation of whole, characterful individuals deeply rooted in their own cultural values